Leptin alters energy intake and fat mass but not energy expenditure in lean subjects - Chrysafi, Pavlina; Perakakis, Nikolaos; Farr, Olivia M.; Stefanakis, Konstantinos; Peradze, Natia; Sala-Vila, Aleix; Mantzoros, Christos S. (Nature communications, 2020)
Based on studies in mice, leptin was expected to decrease body weight in obese individuals. However, the majority of the obese are hyperleptinemic and do not respond to leptin treatment, suggesting the presence of leptin tolerance and questioning the role of leptin as regulator of energy balance in humans. We thus performed detailed novel measurements and analyses of samples and data from our clinical trials biobank to investigate leptin effects on mechanisms of weight regulation in lean normo- and mildly hypo-leptinemic individuals without genetic disorders. We demonstrate that short-term leptin administration alters food intake during refeeding after fasting, whereas long-term leptin treatment reduces fat mass and body weight, and transiently alters circulating free fatty acids in lean mildly hypoleptinemic individuals. Leptin levels before treatment initiation and leptin dose do not predict the observed weight loss in lean individuals suggesting a saturable effect of leptin. In contrast to data from animal studies, leptin treatment does not affect energy expenditure, lipid utilization, SNS activity, heart rate, blood pressure or lean body mass. Leptin treatment is effective to reduce body weight in animal models, but patients with obesity and associated hyperleptinemia do not respond well to leptin therapy. Here the authors report a retrospective analysis of four clinical trials in normo- and mildly hypoleptinemic individuals and show that leptin therapy alters food intake in the short term and reduces weight and fat mass in the long term without effects on energy expenditure.